Using compound sentences to enhance writing skills for children with learning disabilities by Bruce Salder and others - Al-Ghamdi, Lulu Ahmed (Journal of Educational and Psychological Sciences, 2019)
This study aimed to provide a method for building complex sentences to enhance the writing skills of children with learning disabilities by Bruce Salder and others. "The study used the inductive descriptive research methodology. The tool was to summarize (3) major research studies that provided support for using the combination of sentences method as a method to improve students' ability to build Sentences and improving the quality of writing and the number of reviews, the study consisted of an introduction, two papers, and a conclusion.The results of these three studies showed the effectiveness of using this method as a method to improve the capacity of sentence structure. Moreover, these studies have proven the effectiveness of this method with young writers despite their different abilities, including writers with learning difficulties, which in turn affects the quality of formations and the amount of revisions. In light of the results of the study, a number of recommendations and proposals were made to use complex sentences to enhance the writing skills of children with learning disabilities and ensure their success.
Keywords: writing; combining sentences; syntax; academic instructions; sentence structure